Modification of Cu3(BTC)2 with Cobalt Ion for Adsorption and Visualized Detection of Formaldehyde Gas. (20th May 2020) - Gong, Wenpeng; Zhang, Li; Yu, Ying; Lin, Bixia; Wang, Yumin; Cao, Yujuan; Guo, Manli
Abstract : In this paper, cobalt ion was employed to modify Cu3 (BTC)2 to improve the adsorption property for formaldehyde gas. The cobalt ion was doped during the synthesis of Cu3 (BTC)2 to form a product of CuCo‐BTC. As the optimization assay indicated, when the molar ratio of the Co 2+ /Cu 2+ was 3/17, the adsorption amount for formaldehyde gas achieved the maximum, which is 1.6‐fold to that of Cu3 (BTC)2 . ICP‐MS, XPS, XRD, FT‐IR, SEM and N2 adsorption–desorption were used to investigate the structure and property of the CuCo‐BTC. Subsequently, the adsorption kinetic process of the CuCo‐BTC was assessed, the result suggests it coinciding to the pseudo first‐order kinetic model which belongs to the physical adsorption process. The further assays indicated the CuCo‐BTC possessing higher and faster colorimetric response to formaldehyde with indicator than other metal organic framework materials or common indicators. Therefore, it was utilized to fabricate a functional paper chip to perform the visualized detection of formaldehyde gas. The result displayed a sensitive response to formaldehyde gas in the concentration range of 0.02 0.08 mg/m 3 . Besides, the whole colorimetric assay merely takes 150 s, suggesting a favorable application prospect in the on‐site test of detrimental gas. Abstract : A new bimetallic CuCo‐BTC was prepared via modifying Cu3 (BTC)2 with cobalt ion. The adsorption capacity of the CuCo‐BTC to formaldehyde gas increased 1.6‐fold to that of Cu3 (BTC)2 . The CuCo‐BTC was further employed to fabricate a functional paper chip for the visualized detection of formaldehyde gas with indicator, the assays displayed a sensitive colorimetric response to the target in the concentration range of 0.02 0.08 mg/m 3 within 150 s.